Purification and cytotoxic assays of four antimicrobial metabolites extracted from Actinomycetes of the soils of Menengai Crater, Kenya - Waithaka, P.N.; Mwaura, F.B.; Wagacha, J.M.; Gathuru, E.M.; Githaiga, B.M. (Novel Research in Microbiology Journal)
The search for antibiotic metabolites is increasing due to drug resistance been witnessed today. This study was conceived to isolate, identify and compare the antimicrobial metabolites yield of four actinomycetes isolated from Menengai crater soil, Kenya. The actinomycetes were isolated using starch casein, Luria Bertani (M1) and starch nitrate agar. The antimicrobial metabolites were extracted using standard techniques followed by purification, test for antagonism against selected pathogenic microbes, and cytotoxicity assay using Brine shrimp lethality test. Totally, 138 actinomycetes isolates were obtained from all the soil samples. Four isolates showed the highest potent potential against selected bacterial and fungal pathogens. The selected actinomycetes were coded; PAN 30, PAN 37, PAN 41, and PAN 154, and preserved at 4°C for further analysis. The difference in yield of the antimicrobial metabolites between liquid and solid-state fermentation was statistically significant (P= 0.005). Zones of inhibition did not vary significantly (F = 6.6046, P = 0.001338). The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) of the antimicrobial metabolites extracted from PAN 30, PAN 37, PAN 41 and PAN 154 isolates were equal. The Half Lethal Concentration (LC50) in (µg/ ml) for the antimicrobial metabolites extracted from the 4 isolates were; PAN 30 (1.8168 ± 0.47), PAN 37 (3.4269 ± 0.56), PAN 41 (3.4269 ± 0.45), and PAN 154 (4.9397 ± 0.41). The four actinomycetes produced bioactive metabolites. Solid-state fermentation was superior to liquid-state fermentation in recovering the antimicrobial metabolites from the actinomycetes isolates. Molecular identification of the selected isolates needs to be carried out in a future study. Moreover, there is a need to determine the structure of the antimicrobials using nuclear magnetic resonance.